Pre-Reducing Process Kinetics to Recover Metals from Nickel Leach Waste Using Chelating Resins. (9th October 2018) - Botelho Junior, Amilton Barbosa; Dreisinger, David Bruce; Espinosa, Denise Crocce Romano; Tenório, Jorge Alberto Soares
Abstract : The main problem of the separation process from nickel mining using the ion exchange technique is the presence of iron, which precipitates in pH above 2.00 and causes coprecipitation of copper and cobalt. Chelating resins have the main advantage of being selected for a specific metal present in solution. Studies have been developed to increase the efficiency of metals recovery using chemical reduction and the ion exchange process to recover metals. The aim of this work was to use sodium sulfite as a reducing agent to convert Fe(III) to Fe(II). Chelating resins Lewatit® TP 207, selective for copper, and Lewatit® TP 220, selective for nickel and cobalt, were studied. Batch experiments were performed to study the effect of pH with and without sodium sulfite. Results indicated that the industrial process has increased efficiency when the reducing process is applied.